2017
DOI: 10.1080/08853908.2017.1288182
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Intra-GCC Food Trade

Abstract: Using panel data for six Gulf Cooperation Council (GCC) countries from 1995-2014, we assess the impacts of several major economic variables on intra-GCC food exports, and on GCC food exports to the world. The GCC customs union had minimal impact on intra-GCC food exports, but occasioned a significant reduction in GCC food exports. Unlike GCC food exports, intra-GCC food exports occurred among countries with similar relative factor endowments, in agreement with the Linder Hypothesis. Rising incomes and exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…In the food trade, Linder’s hypothesis is able to identify the existence of economic similarities that also influence exports in terms of food consumption preferences (Steinbach, 2015). The significant influence of relative factor endowment on food export is in line with the findings of Kaitibie and Rakotoarisoa (2017) and Ferto and Jambor (2015) that the negative coefficient of relative factor endowment indicated that the higher difference in factor endowment between trade partners affect negatively food export. In other words, it means that the smaller factor endowment could boost food export because the similarity of factor endowment between trade partners.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…In the food trade, Linder’s hypothesis is able to identify the existence of economic similarities that also influence exports in terms of food consumption preferences (Steinbach, 2015). The significant influence of relative factor endowment on food export is in line with the findings of Kaitibie and Rakotoarisoa (2017) and Ferto and Jambor (2015) that the negative coefficient of relative factor endowment indicated that the higher difference in factor endowment between trade partners affect negatively food export. In other words, it means that the smaller factor endowment could boost food export because the similarity of factor endowment between trade partners.…”
Section: Resultssupporting
confidence: 84%
“…Therefore, it is not surprising that in empirical research related to international trade the gravity of trade model is one of the models that is widely used by researchers (Kashiwagi et al , 2020), including in studies related to the export of food commodities, such as food export on intra-GCC countries (Kaitibie and Rakotoarisoa, 2017), Iranian exported tomatoes (Ehsan Zohoori et al , 2018), Pakistani rice export (Irshad et al , 2018), Vietnam’s rice export (Thuong, 2018), Ethiopia’s coffee export (Bekele and Mersha, 2019), Nigeria’s cocoa export, Algeria’s agricultural export (Matallah et al , 2021), Vietnam’s rice and coffee (Nguyen, 2022) and global trade of rabbit meat export (Wu, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…[16] According to the annual statistics of food consumed in the Gulf Cooperation Council (GCC), in 2017, Saudi Arabia was on the upper side of the list of GCC countries in terms of the amount of annual consumed food. [69] In 2012, the amount of consumed food in the country totaled 25.8 million metric tons, compared to 29.6 million metric tons in 2014 (961.6 kg per capita). [70] This is of particular relevance to the present study since adolescents have become especially vulnerable to extreme marketing efforts by business companies to advertise unhealthy snacks since they represent future adult consumers.…”
Section: Female Adolescents In Saudi Arabiamentioning
confidence: 99%
“…2 Several recent articles in the ITJ have looked at how other regional trade agreements have affected trade (Kaitibie and Rakotoarisoa 2017;Montant 2020). came into effect.…”
Section: From the Editormentioning
confidence: 99%